Perancangan Sistem Administrasi Zakat Dan Infaq Berbasis Web Menggunakan Metode Extreme Programming (Studi Kasus : Yayasan An-nahdhiyin): Perancangan Sistem Administrasi Zakat Dan Infaq Berbasis Web Menggunakan Metode Extreme Programming (Studi Kasus : Yayasan An-nahdhiyin) - Muhamad Syahril Hidayatulloh Syahril; Wasis Haryono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Administration system Is a system that provides services in the form of notes, correspondence in managing data. The existence of this administrative system is very important. In this case, the An Nahdhiyin Foundation is used as a place of research, because the existing administrative system at the An Nahdhiyin Foundation has not been managed properly so that it often complicates the implementation of existing management and activities, such as the process of inputting zakat and infaq funds.The purpose of this study is to provide convenience when managing zakat and infaq funds, errors in recording data, increasing data security, and managing the transparency of existing zakat funds. And the purpose of the research resulted in several uses consisting of practical uses and academic uses.The research method used in this research is using a qualitative method. While the development of the system using the Extreme Programming method. The software used is: Windows 10, and XAMPP V.3.3.0. The result of this research is a web application called "Zakat and Infaq Administration System Using Extreme Programming Method (case study: An Nahdhiyin Foundation)" a web created to facilitate data management activities at An-nahdhiyin Foundation.